Some factors affecting properties and dissolution behavior of tablet furosemide microspheres - (:unkn) unknown (My University, 1992)
Furosemide (1) microspheres prepared by using Eudragit® RS (1:4 and 1:2 drug:polymer ratios) were tableted. Microspheres were compressed with or without excipients (lactose, Avicel® PH 101 or Emcompress®). The thickness and crushing strength of tablets containing excipients were also found to be affected by the type of excipients. Dissolution characteristics of furosemide from tableted microspheres with or without excipients depended on the applied compression force but showed a controlled release behavior. Compression slowed down the release of 1. Addition of excipients to the formulation increased drug dissolution. The release from tablets followed Higuchi matrix model kinetics.